Upper Bound Analysis of the Stability of 3D Slopes in the Saturated Soft Clay Subjected to Seismic Effect - Zhang, Biao; Jiang, Yi; Cheng, Hao; Liu, Ze (Frontiers in Earth Science, 2021)
In order to study the three-dimensional stability problem of the saturated soft clay slope under earthquake loads. Based on the three-dimensional rotation failure model, the seismic force was introduced into the calculation by the quasi-static method. The work rate of external loads and internal energy dissipation rate of the saturated soft clay slope was calculated via the upper bound method of limit analysis, and the analytical solution of stability coefficient of saturated soft clay slopes was derived based on the fictitious power principle. By virtue of the exhaust algorithm, the optimal solution of stability coefficient of saturated soft clay slopes was obtained. The influence of the slope angle and the horizontal and vertical seismic forces on the stability coefficient of saturated soft clay slope was analyzed. The results show that the slope angle has a great influence on the stability coefficient, and the relative difference is up to 35.7%. Therefore, the stability coefficient of saturated soft clay slopes can be effectively increased by proper slope setting. The horizontal and vertical seismic forces also have significant influence on the stability of saturated soft clay slopes. The relative differences of stability coefficient under horizontal and vertical seismic forces are as high as 41% and 14.7% respectively. If they are ignored, the stability coefficient of saturated soft clay slopes will be seriously overestimated. It is suggested that the effects of horizontal and vertical seismic forces must be considered simultaneously in the seismic design of saturated soft clay slopes.